Nurse managers’ strategies promoting a Fundamentals of Care-based approach among nurses: A scoping review - Lombardì Fortino, D.; Galazzi, A.; Chiappinotto, S.; Palese, A. (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Introduction. In the last few years, shortcomings in caring for patient needs have promoted a growing interest in the Fundamentals of Care (FoC) to promote the quality of nursing care. However, which strategies nurse managers should implement to facilitate a FoC-based nursing care approach have not been mapped to date; therefore, the intent of this study was to map those strategies related to the nurse manager role that have been documented as being capable of promoting (or hindering), a FoC-based approach among nurses. Methods. A scoping review following the Preferred Reporting Items for Systematic Review and MetaAnalysis – Extension for Scoping Reviews (PRISMA-ScR) guidelines. The PubMed, CINAHL, Cochrane Library, Scopus and Web of Science databases and the conference proceedings of the International Learning Collaborative 2022 Annual International Conference were consulted. Studies exploring the relationship between FoC and nurse managers using any methodology, published from 2008 (year of birth of the FoC movement) to September 2022, in Italian or English, were eligible for inclusion. Findings were categorized narratively, according to their similarities and differences. Results. Four qualitative studies, four discussion papers, two reviews and one mixed-method study, published from 2017 to 2021, predominantly in Australia, were included. Several strategies have emerged as promoting a FoC-based care approach by nurse managers. At the macro level, there is a need to disseminate a culture of attention towards patients that should be incorporated in the strategy of the entire system; moreover, synergies and effective leadership styles should be promoted by also providing education both in the undergraduate and continuing education settings. At the micro levels, among others, the required resources should be available, and the quality of the environment promoted.Conclusion. Nurse managers may facilitate a FoC-based approach among nurses through a set of strategies that should be included and considered in their educational pathways